A scalable Web cache consistency architecture. - Yu, Haobo
The rapid increase in web usage has led to dramatically increased loads on the network infrastructure and on individual web servers. To ameliorate these mounting burdens, there has been much recent interest in web caching architectures and algorithms. Web caching reduces network load, server load, and the latency of responses. However, web caching has the disadvantage that the pages returned to clients by caches may be stale, in that they may not be consistent with the version currently on the server. In this paper we describe a scalable web cache consistency architecture that provides fairly tight bounds on the staleness of pages. Our architecture borrows heavily from the literature, and can best be described as an invalidation approach made scalable by using a caching hierarchy and application-level multicast routing to convey the invalidations. We evaluate this design with calculations and simulations, and compare it to several other approaches.
Keywords: Computer systems organization; Computer communication networks; Local and wide area networks; Internet (e.g., TCP/IP).; Design; Measurement; Performance; Standardization; Theory